2016
DOI: 10.1007/s00330-016-4395-2
|View full text |Cite
|
Sign up to set email alerts
|

Short & long term adverse outcomes after arterial embolisation for the treatment of postpartum haemorrhage: a systematic review

Abstract: • Embolisation for PPH does not adversely affect menstrual cycle and fertility • Experience of life-threatening PPH might prevent couples from pursuing another pregnancy • Pathological placentation seems to occur more frequently after embolisation for PPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 88 publications
1
32
1
2
Order By: Relevance
“…Follow-up studies of women who have undergone arterial embolisation for control of PPH suggest that the intervention does not impair subsequent menstruation and fertility. [108][109][110] Evidence level 3…”
Section: Evidence Level 2++mentioning
confidence: 99%
See 1 more Smart Citation
“…Follow-up studies of women who have undergone arterial embolisation for control of PPH suggest that the intervention does not impair subsequent menstruation and fertility. [108][109][110] Evidence level 3…”
Section: Evidence Level 2++mentioning
confidence: 99%
“…Other additional risk factors include maternal age 110,113,117,120 and ART, in particular in vitro fertilisation. 113,120,[122][123][124][125] Advanced maternal age (35 years or more) in women without a previous caesarean section increases the aOR by 1.30 (95% CI 1.13-1.50) for every 1-year increase in age.…”
Section: Evidence Level 2+mentioning
confidence: 99%
“…7 Winograd et al and Soro et al presented internal iliac artery catheterization and embolization for pelvic devascularization, yet it still holds the need for trained interventional radiologist, with the use of expensive machinery. 8,9 Estimated blood loss was roughly by weighing of laparotomy pads before and after soiling and amount in suction apparatus. The use of balloon compression, as Bakri Balloon, has also been proposed in cases of placenta accreta.…”
Section: Discussionmentioning
confidence: 99%
“…If bleeding persists, further measures include insertion of a Balloon-tamponade of the uterus, surgical intervention such as uterine compression sutures (B-Lynch, Hayman technique, or others [52]) or uterine vessel mass ligation. In haemodynamically stable patients, emergent transfer to interventional radiology department and uterine artery embolization may be an effective and often successful intervention [53]. Finally, hysterectomy might become necessary as ultima ratio if other measures were unsuccessful.…”
Section: Management Of the Woman During Deliverymentioning
confidence: 99%
“…Balloon tamponade can also can be used to bridge the time until embolization. Longitudinal trials in patients who underwent arterial embolization to manage PPH showed that this method does not affect the following menstruation cycles or fertility [53]. If artery ligation failed, selective arterial occlusion might be considered [107].…”
Section: Embolizationmentioning
confidence: 99%